(untitled) (Applied Biological Research, 2023)
This study reveals the distributional patterns and relationship of benthic macroinvertebrate assemblages to their environments in a lesser known river Dhasan (a tributary of river Bentwa) of Central India. Extensive sampling was done (20 quadrates per station) in winter season (December 2018 to February 2019). The total mean density of river decreased from S1 to S4 (except S2) and differed significantly among the stations. A total of 15 (family) were observed among all the stations. Among these, Caenidae was most abundant taxon at S1 while Thiaridae was abundant from S2 to S4. The assemblages forming taxa varied from S1 to S4. Longitudinally, the abundance ofCaenidae and Viviparidae declined from S1 to S4, but Chironomidae and Gomphidae increased from S1 to S4. Similarly, the abundance of Tabanidae and Thiaridae also increased from S1 to S4, but decline at S3. Canonical correspondence analysis indicated current velocity as the most important variable for faunal distribution. Functionally, the river was separated in two zones; heterotrophic (S1 to S3) to autotrophic S4). The abundance of collectors and gathers resulted in heterotrophic condition while scrappers for autotrophic condition. Hence, two ecological zones are evident in the river Dhasan.